Exploring the Murder Trials effect on Judges’ Psychological and Mental Health: A Qualitative Study - Ullah Khan, Asad (Annals of Human and Social Sciences, 2023)
Judges hearing murder Trials are mostly exposed to negative and violent information continuously. And affected by the Trials psychologically. Purpose of this research is to explore and describe the psychological and mental health issues among Judges who hear murder Trials. Judges face emotional issues but they have to regulate their emotions and handle the professional glitches effectively for affective decision making. Purposive sampling strategy was employed. Qualitative interpretive phenomenology research method was used and semi structured interviews were conducted for data collection. Results explored on the basis of face to face interviews and codes, categories and themes were originated. Results revealed, Judges who hear murder Trials are affected psychologically and their mental health is affected. They have to focus on communication proficiency because it can help to express what they face or feel. With the strategies to cope up with emotional issues and its regulation Judges can be in position to handle professional glitches at workplace.